Liver and spleen transcriptome reveals that Oreochromis aureus under long-term salinity stress may cause excessive energy consumption and immune response. Issue 107 (December 2020) - Zhou, Kangqi; Huang, Yin; Chen, Zhong; Du, Xuesong; Qin, Junqi; Wen, Luting; Ma, Huawei; Pan, Xianhui; Lin, Yong
Abstract: To investigate the physiological responses of Oreochromis aureus to salinity fluctuations at the molecular level. We used RNA-seq to explore the differentially expressed genes (DEGs) in the liver and spleen of O. aureus at 0, 3, 7 and 11 ppt (parts per thousand) salinity levels. Herein, De novo assembly generated 71, 009 O. aureus unigenes, of which 34, 607 were successfully mapped to the four major databases. A total of 120 shared DEGs were identified in liver and spleen transcripts, of which 83 were up-regulated and 37 were down-regulated. GO and KEGG analysis found a total of 26 significant pathways, mainly including energy metabolism, immune response, ion transporters and signal transduction. The trend module category of DEGs showed that the genes (e.g., FASN, ODC1, CD22, MRC, TRAV and SLC7 family) involved in the change-stable-change (1) and the constant-change categories (2) were highly sensitive to salinity fluctuations, which were of great value for further study. Based on these results, it would help provide basic data for fish salinity acclimation, and provide new insights into evolutionary response of fish to various aquatic environments in the long-term stress adaptation mechanism. Highlights: Using RNA-Seq technology for the first time to obtain Oreochromis aureus liver and spleen transcript data under different salinity stress. In order to maintain osmotic pressure balance, the liver of Oreochromis aureus will produce more fat or carbohydrates to provide energy for it. Long-term salinity stress will make the spleen of Oreochromis aureus more immune stress, which can potentially improve the body's disease risks. This study identified some functional genes (e.g. FASN, OCD1 and SLC7 family etc.) that may be involved in salt adaptation.